2005
DOI: 10.1542/peds.2005-0392
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Withholding or Withdrawing Care to Newborn Mortality

Abstract: The majority of nursery deaths of infants born in our hospital occurred as the result of selected noninitiating of care or as a result of withdrawing care in infants not responding or considered to have a futile outcome. Only slightly more than one quarter of the infants received total care until the time of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 6 publications
3
32
2
Order By: Relevance
“…The findings are consistent with those of previous studies in China, Croatia and Uganda that showed that babies with low Apgar score are more likely to die during the perinatal period (15)(16)(17)(18)(19). Our study showed that nearly a half of the cases (babies who died) were fresh still births.…”
Section: Discussionsupporting
confidence: 93%
“…The findings are consistent with those of previous studies in China, Croatia and Uganda that showed that babies with low Apgar score are more likely to die during the perinatal period (15)(16)(17)(18)(19). Our study showed that nearly a half of the cases (babies who died) were fresh still births.…”
Section: Discussionsupporting
confidence: 93%
“…2 The commonly used lifesustaining practices include maximal intensive care, redirection of intensive care (limited care or withdrawal of care), and primary nonintervention care. [2][3][4][5] However, decision-making practices have been reported to vary widely from country to country and among different institutions in the same country. [6][7][8][9] These differences are mainly related to prognostic uncertainty 10 and combine the interface between the "disease-oriented" and the "person-oriented" approaches, together with the individual case-related circumstances, namely, the family, the medical team, law, and society.…”
mentioning
confidence: 99%
“…At many institutions, including ours, the practices and policies of withholding and withdrawing care have been studied and modified. [6][7][8][9][10] At LAC þ USC, 72% of deaths from 1993 to 2002 resulted from care not initiated or care withdrawn. 6 We believe that such intense interest with respect to infant quality of life has resulted in fewer postponed deaths in the postneonatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was shown that while extreme prematurity made up 60% of cases in which care was not initiated at birth, congenital anomalies only made up 33% of the cases. 6 This may account for the increasing percentage of postneonatal deaths made up by congenital anomalies.…”
Section: Discussionmentioning
confidence: 99%